2017
DOI: 10.3390/ijgi6090261
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Google Street View with Virtual Reality: A Motivational Approach for Spatial Training Education

Abstract: Abstract:Motivation is a determining factor in the learning process, and encourages the student to participate in activities that increase their performance. Learning strategies supplemented by computer technology in a scenario-based learning environment can improve students' motivation for spatial knowledge acquisition. In this sense, a workshop carried out with 43-second year engineering students supported by Google Street View mobile geospatial application for location-based tasks is presented, in which par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…On the application of DVR/WVR (for simulations, digital games, and virtual worlds) in geography teaching and learning see List & Bryant, 2014;Luo et al, 2016;and Tüzün et al, 2009. Experimental studies (conducted on all levels of education) showed that IVR (with the use of HMDs) could have a positive influence on students' motivation and improve learning outcomes for various geographic contents and skills, such as: astronomy and mathematical geography (Hussein & Nätterdal, 2015;Madden et al, 2018), cartography and spatial orienta- Web and GIS technologies Source: Stojšić et al, 2018;based on: Huang et al, 2001 tion (Carbonell- Carrera & Saorín, 2017;Šašinka et al, 2019), climate change and ecological awareness (Bailenson, 2018;Markowitz et al, 2018), physical, social and regional geography -virtual field trips (Minocha et al, 2017;Vishwanath et al, 2017). More about when and how to use this technology in education, about ethical and safety issues and recommended time limit for the use of HMDs (up to 15 or 20 minutes) see Bailenson, 2018;Southgate et al, 2018;and Stojšić et al, 2019.…”
Section: Vr In Geography Teaching and Learningmentioning
confidence: 99%
“…On the application of DVR/WVR (for simulations, digital games, and virtual worlds) in geography teaching and learning see List & Bryant, 2014;Luo et al, 2016;and Tüzün et al, 2009. Experimental studies (conducted on all levels of education) showed that IVR (with the use of HMDs) could have a positive influence on students' motivation and improve learning outcomes for various geographic contents and skills, such as: astronomy and mathematical geography (Hussein & Nätterdal, 2015;Madden et al, 2018), cartography and spatial orienta- Web and GIS technologies Source: Stojšić et al, 2018;based on: Huang et al, 2001 tion (Carbonell- Carrera & Saorín, 2017;Šašinka et al, 2019), climate change and ecological awareness (Bailenson, 2018;Markowitz et al, 2018), physical, social and regional geography -virtual field trips (Minocha et al, 2017;Vishwanath et al, 2017). More about when and how to use this technology in education, about ethical and safety issues and recommended time limit for the use of HMDs (up to 15 or 20 minutes) see Bailenson, 2018;Southgate et al, 2018;and Stojšić et al, 2019.…”
Section: Vr In Geography Teaching and Learningmentioning
confidence: 99%
“…Most of the recent user studies in cartography use either only static 3D maps or interactive 3D maps as stimuli, not both. Static stimuli have been used, for example, by Schobesberger and Patterson [9], Engel et al [18], Niedomysl et al [19], Popelka and Brychtová [20], Seipel [21], Popelka and Doležalová [22], Preppernau and Jenny [23], Rautenbach et al [24], Zhou et al [25], and Liu et al [26], whilst interactive stimuli have been used by Abend et al [27], Wilkening and Fabrikant [28], Treves et al [29], Špriňarová et al [30], McKenzie and Klippel [31], Carbonell-Carrera and Saorín [32], and Herman et al [33].…”
Section: Static Versus Interactive 3d Mapsmentioning
confidence: 99%
“…It is essential for investigating and monitoring the most important geomorphological features of natural areas. The rich potential of 3D rendering is also utilized in areas that rely on geographical data, for example, evacuation planning [1], geospatial data exploration and analysis [2][3][4], navigation in urban areas [5,6], visualization of spatial data quality [7], educational games [8], and urban planning [9]. It is also possible to use the interaction between other digital information for 3D terrain rendering for disaster prediction and in (geographic) education.…”
Section: Introductionmentioning
confidence: 99%